PENGARUH KETERSEDIAAN ENERGI LISTRIK TERHADAP PDRB DI PROVINSI ACEH - Helmy Helmy; Teuku Zulham (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract The Central Government is seriously concerned with equitable development and development in all regions of Indonesia, including in the energy distribution. This study aims to determine the effect of the availability of electrical energy on economic growth in Aceh Province which is seen through GRDP. This study use secondary data through institutions and agencies related to the data used is data on the availability of electrical energy and GDP of Aceh Province. The analysis model use the Simple Linear Regression analysis method with the classic assumption test and hypothesis testing to get maximum results. The results of this study indicate that the availability of electricity influences economic growth in Aceh Province, and it can be seen that any increase in the variable availability of electrical energy will affect economic growth as seen from the increase in GRDP. Keywords: GRDP, Electric Energy, Aceh Province